Precisely Controlling Polymer Acceptors with Weak Intramolecular Charge Transfer Effect and Superior Coplanarity for Efficient Indoor All-Polymer Solar Cells with over 27% Efficiency - Zou, Bosen (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.